Levels of superoxide dismutase and malondialdehyde in primary spontaneous pneumothorax - Erhan Tabakoglu; Senturk Ciftci; Osman Nuri Hatipoglu; Gündeniz Altıay; Tuncay Caglar (Hindawi Limited, 2004)
THE aim of the present study is to determine whether patients with primary spontaneous pneumothorax (PSP) are subject to oxidative stress. For this purpose, we measured the activities of red blood cell superoxide dismutase, which is an antioxidant enzyme, and the level of plasma malondialdehyde, which is one of the lipid peroxidation markers, in a group of patients with PSP. The study was carried out with 16 patients with PSP and 24 healthy individuals. The two groups were similar to each other in terms of sex, age and smoking attitudes. Erythrocyte superoxide dismutase activity was found to be significantly lower in patients with PSP than in the control group (p<0.01). The plasma malondialdehyde levels were significantly high in patients with PSP (p<0.01). Our results suggest that oxidative stress may contribute to the pathogenesis of PSP.